Принципи кооперативного права - Семчик, В.І. (Альманах права, 2012)
У статті проаналізовано фундаментальну концепцію кооперації, визначено характерні особливості організації кооперативів і кооперативних систем. Крім того, надано класифікацію кооперативних принципів, та охарактеризовані їх особливості. Також здійснено порівняння міжнародних кооперативних принципів і кооперативної практики з основними кооперативними принципами і практикою їх застосування в Україні. На підставі всебічного аналізу кооперативних принципів і деяких аспектів кооперативної практики визначено основоположні засади, форми і межі втілення кооперативних принципів на законодавчому рівні. В статье проанализирована фундаментальная концепция кооперации, определены характерные особенности организации кооперативов и кооперативных систем. Кроме того, осуществлена классификация кооперативных принципов, и охарактеризованы их особенности. Также проведено сравнение международных кооперативных принципов и кооперативной практики с основными кооперативными принципами и практикой их применения в Украине. На основании всестороннего анализа кооперативных принципов и некоторых аспектов кооперативной практики определены основополагающие принципы, формы и пределы реализации кооперативных принципов на законодательном уровне. The article analyzes the fundamental concept of cooperation, defines the characteristics of cooperatives and cooperative systems. In addition, it is given the classification of cooperative principles, and their main features are described. The principles of voluntary and open membership, democratic governance, economic participation, autonomy and independence, education, training and information, cooperation among cooperatives, benefit of association are reviewed. The main purpose of the cooperative law principles is embodying in the legislation a joint cooperative policy, based on cooperative ideas and fundamental cooperative concepts. The principles of cooperative law are defined by the constitutional principles: the supremacy of law; declaration humans life and health, honor and dignity, inviolability and security as the highest social value; determination of human rights and freedoms and their guarantees as the essence and orientation of the state activity; admission of the states responsibility for its activity, etc. The main role of the educational principle is noted. According to this cooperative principle to provide the actual development of the cooperatives their members, elected representatives, administrative staff and employees should be educated and trained due to the needs of cooperative. Also the comparison of international cooperative principles and practices with main Ukrainian cooperative principles and practices is made. Based on comprehensive analysis of cooperative principles and some aspects of cooperative practices, the basic principles, forms and limits of the cooperative principles implementation to the Ukrainian legislation are defined.